Preface - Uzakov Gulom; Abdullozoda Ramazon; Bovtrikova Elena; Gibadullin Arthur; Toshmamatov Bobir; Morkovkin Dmitry; Sadullozoda Shahriyor (E3S Web of Conferences, 2023)
Within the framework of the presented material, the results of the conducted VI International Conference on Actual Problems of the Energy Complex and Environmental Protection (APEC-VI-2023).